Investigation of main particulars subject to minimum building cost for chemical tankers - Celik, Fahri; Erturk, Ibrahim; Turan, Eda (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
The maritime transportation sector is rapidly growing depending on the global growth, hence chemical tanker shipping is positively being affected concordantly. Detailed analyses are required to define costs accurately at the preliminary design stage as shipbuilding projects require high levels of financing which may be affected by daily price fluctuations in the global economic system. In this study, empirical formulas are derived in order to estimate the principal particulars, main engine power, weight components and costs of the chemical tankers less than 30,000 DWT in the preliminary design stage. Utilizing the formulas that are derived from the data of recently built vessels; an approach based on systematic analysis method is presented to determine the principle particulars of the optimum vessel subject to minimum building costs of chemical tankers, which have different speeds and tonnages. In this study, three applications for the estimation of preliminary design parameters and investigation of optimum particulars are carried out. Consequently, it is shown that the preliminary design parameters can be estimated with fairly low errors and initial building costs can be decreased by up to 9% by optimizing the main particulars. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Chemical tankers; Shipbuilding cost; Preliminary design; Systematic analysis; Engineering; Oceanography